Glass Cliff Phenomenon: How Do Women in Senior Leadership Positions in Nigeria Perceive Their Leadership Experience - Ginger- Eke, Onyekachi (Digital Repository of Theses, 2026)
This study explored the gendered experiences of women in senior leadership positions in Nigeria, with a focus on the “glass cliff” phenomenon — the tendency for women to be appointed to precarious leadership roles during times of crisis. Drawing on a critical theoretical lens, the research investigated how structural, cultural, and organizational forces shape women’s access to leadership, their experiences within maledominated institutions, and their strategies for resisting and reimagining power. Using a qualitative methodology, in-depth interviews were conducted with twenty women across diverse sectors who occupy or have occupied senior leadership roles. A hybrid approach of deductive and inductive thematic analysis was used to surface both anticipated and emergent themes within their narratives. Pre-interview questionnaires supported contextual understanding and triangulation. Findings reveal that while formal barriers to leadership may be shifting, informal gatekeeping, cultural and religious norms, symbolic scrutiny, and emotional labor continue to restrict women’s leadership experiences. The “glass cliff” was evidenced through patterns of appointment during organizational instability and expectations of unreciprocated emotional and symbolic labor. Despite these challenges, women demonstrated quiet but strategic resistance — mentoring others, advocating for institutional reform, and modeling authentic leadership on their own terms. This research contributes to gender and leadership scholarship in African contexts by highlighting the persistence of hidden power structures and the agency women deploy to navigate and transform them. It calls for inclusive leadership policies, institutional reforms, and ecosystem-wide strategies to support and sustain women in leadership